Comparison of de novo and upgrade to resynchronization therapy: a propensity-score matched analysis. (25th November 2020) - Brandao, M; Goncalves Almeida, J; Monteiro, J; Montenegro Sa, F; Fonseca, P; Rosas, F; Santos, E; Ribeiro, J; Oliveira, M; Goncalves, H; Primo, J; Braga, P
Abstract: Background: Upgrade to resynchronization therapy (CRT) from conventional pacemaker (P) or defibrillator (D) is common practice in Europe. However, guidelines (GL) are discordant: Pacing GL give a class I recommendation, while Heart Failure (HF) GL provide a class IIb indication. Previous studies suggested worse outcomes in upgraded patients (pts). Aim: To compare response rate and clinical outcomes in a cohort of pts receiving de novo or upgrade to CRT. Methods: Single-center retrospective study of consecutive pts submitted to CRT implantation (2007–2017). Major adverse cardiac events (MACE) included HF hospitalization (HHF) or all-cause mortality. Clinical response was defined as New York Heart Association class improvement without MACE in the first year of follow-up (FU). Left ventricle end-systolic volume reduction of >15% denoted echocardiographic (echo) response. Survival analysis with Kaplan-Meier method and Log-rank test was performed. Propensity-score matching (PSM) analysis was made to adjust for possible confounder variables. Results: 230 CRT recipients (70.9% male, mean age 67±11 years, 71.5% non-ischemic cardiomyopathy, 39.6% CRT-P) were included, of whom 46 (20%) underwent an upgrade. Upgraded pts were older (69.8 vs 65.9 years, p=0.015), with higher rates of permanent atrial fibrillation (37.0% vs 12.7%, p=0.001), moderate to severe valve disease (45.7% vs 22.3%, p=0.002), chronic kidney disease (37.0% vs 17.2%, p=0.005) and treatment with mineralocorticoid receptor antagonists (79.1% vs 52.0%, p=0.002). They were more likely to receive CRT-P (65.2% vs 33.2%, p<0.001) and CRT-D were more often implanted for secondary prevention (60.0% vs 17.9%, p=0.001). No differences emerged in procedural complications, clinical (74.4% vs 71.4%, p=0.712) or echo (66.7% vs 69.7%, p=0.822) response rates. During a median FU of 3±4 years, all-cause mortality was similar among groups (Log Rank test, p=0.522, unadjusted hazard ratio [HR] 1.25, confidence interval [CI] 95% 0.62–2.49, p=0.534). There was a statistical tendency for higher MACE rate in the upgrade group (Log Rank test, p=0.064, HR 1.66, CI 95% 0.95–2, 91, p=0.076). No differences were found in lead dislodgement (10.9% vs 7.1%, p=0.368) or endocarditis (2.2% vs 4.3%, p=0.692) rates. PSM analysis identified 88 matched pairs (46 upgrade/42 de novo pts). In this cohort, all-cause mortality (Log Rank test, p=0.77, HR 0.89, CI 95% 0.39–2.03, p=0.78) and MACE (Log Rank test, p=0.36, HR 1.38, CI 95% 0.68–2.81, p=0.37) were comparable between groups [graph no. 1]. Conclusion: Upgrade to CRT was similar to de novo implantation in terms of complications and clinical and echo response, in this cohort. The risk for MACE and mortality was also comparable. Funding Acknowledgement: Type of funding source: None